Numerical simulation of the processes of small-diameter high-current electron beam shaping and injection - Gordeev, V.S.; Mikhailov, E.S.; Myskov, G.A.; Laptev, D.V. (Вопросы атомной науки и техники, 2001)
With the aid of BEAM25 program there was carried out the numerical simulation of the non-stationary process of shaping a small-diameter (≤ 20 mm) high-current hollow electron beam in a diode with magnetic insulation, as well as of the process of beam injection into the accelerating LIA track. The diode configuration for the purpose of eliminating the leakage of electron flux to the anode surface was updated. Presented are the results of calculation of the injected beam characteristics (amplitude-time parameters of a current pulse, space-angle distributions of electrons etc.) depending on diode geometric parameters.